Quantitative data extraction from orthopyroxene trace element maps and its potential to examine the formation of the UG2 unit, bushveld complex - Kamber, Balz (My University, 2019)
We present a mineral chemical stratigraphy across the UG2 Unit, situated in the Upper Critical Zone of the Bushveld Complex. The magmatic evolution of the rocks hosting this world-class ore deposit for chromium and platinum group elements (PGEs) is still under debate. Orthopyroxene is a common phase across the magmatic stratigraphy of the unit. It hosts trace metals, whose relative contents can record information about magmatic processes. This study determined laser ablation inductively-coupled plasma mass spectrometry (LA-ICP-MS) trace element data for orthopyroxene and spot LA multi-collector ICP-MS Sr-isotope data for plagioclase. Mapping of trace element distributions revealed internal zoning in Cr, V, Y, and Th. Unlike in conventional spot analysis, quantitative trace element concentrations were extracted post-analysis from two-dimensional LA-ICP-MS maps. This approach offered advantages over spot analysis. The maps revealed internal complexities (e.g., inclusions, exsolved phases, zonations and diffusion halos) that could be avoided with suitable thresholds for chemical filter elements (i.e., 100 ppm < Cr < 4000 ppm, Y < 6 ppm), permitting fast, automated extraction of pure orthopyroxene data pixels from elemental maps covering noritic, troctolitic, anorthositic and chromititic mineral assemblages. Diffusive equilibration in orthopyroxene was evaluated by comparing zonations in elements with different known diffusivities. Magnesium and Ni are homogenously distributed, indicative of rapid diffusive processes, while Cr and V show zonations, interpreted to largely reflect primary distribution. Thorium and Y apparently diffused along discrete pathways, indicated by concentration anomalies following orthopyroxene lamellae. A systematic study of the trace element inventory of orthopyroxene across the succession of the UG2 Unit, complemented with Sr isotope signatures of plagioclase, revealed clear evidence for open-system processes: compatible elements (Cr, Ni) are decoupled from Mg# variations in orthopyroxene from specific UG2 subunits; distinct Mg# peaks coincide with negative V excursions in orthopyroxene from chromite-bearing subunits; towards the top of the unit, plagioclase shows a distinct 87Sr/86Srinitial peak and orthopyroxene shows Cr-depleted and Th-enriched rims. These chemical features cannot be explained by crystal mixing alone and argue for the involvement of at least two chemically distinct melts in the formation of the studied UG2 section
Keywords: LA-ICP-MS; Orthopyroxene; Geochemical mapping; Bushveld complex; UG2 Unit; Mineral chemical stratigraphy; mineral chemical stratigraphy